AKSELERASI PENCEGAHAN DAN PENURUNANSTUNTING MELALUI PENGUATAN PERAN TIM PENDAMPING KELUARGA (PELITA)DI WILAYAH PERBATASAN INDONESIA: PELATIHAN PENGUKURAN ANTROPOMETRI DAN ANGKA KECUKUPAN GIZI BALITA - Gusriani, Gusriani; Ridha, Andi Ahmad; Cahyani, Reni Tri; Wahida, Wahida; Padlilah, Rahmi; Umami, Nurrahmi (Jurnal Pengabdian Masyarakat Borneo, 2024)
Stunting is a major public health issue in Indonesia, particularly in border areas where access to healthcare services is limited. This condition results from chronic malnutrition during the first 1,000 days of life, leading to impaired physical growth, brain development, and reduced intelligence and productivity in the future. Nunukan Regency, specifically in the Sebatik area of North Kalimantan, has a high stunting prevalence, reaching 30.5%, well above the national average.This program aims to accelerate stunting prevention and reduction by strengthening the role of Family Assistance Teams (TPK) through training on anthropometric measurement and the calculation of Nutritional Requirements (AKG) for infants. TPK plays a critical role in early detection of stunting risks and delivering appropriate nutritional interventions at the community level. The training includes awareness-raising, demonstrations, and hands-on practice in anthropometric measurement and the use of a Stunting Infant Nutritional Calculator. Evaluation results from pre-test and post-test assessments show a significant improvement in the knowledge and skills of TPK members. With improved competencies, TPK can provide more accurate nutritional advice to at-risk families, thus supporting national efforts to reduce stunting prevalence. This program is expected to contribute to the reduction of stunting rates in Nunukan Regency, especially in the Sebatik area of North Kalimantan